Carbon isotope discrimination: Potential interest for grain yield improvement in durum wheat - Merah O.; Deléens E.; Araus J.L.; Souyris I.; Nachit M.; Monneveux P. (Durum wheat improvement in the Mediterranean region: New challenges, 2000)
Carbon isotope discrimination (D) has been proposed as a criterion for indirect selection for transpiration efficiency and for grain yield improvement in cereals. To evaluate the genetic variation for D, the relationship between D and grain yield, and to determine the magnitude of genotype x environment (G x E) interactions in durum wheat, field experiments were conducted under Mediterranean conditions. For this purpose, 125 durum wheat accessions from various geographic origins were studied in six trials contrasted for their water availability. Grain yield (GY) and carbon isotope discrimination of the kernel (DK) were measured. A large genotypic variation was noted for DK and GY. Both traits values also differed between environments. This difference was attributed to the variation in water availability. DK and GY were significantly and positively correlated in all environments.
Seminar on Durum Wheat Improvement in the Mediterranean Region: New Challenges, 2000/04/12-14, Zaragoza (Spain)